Factors related to difficult self‐expandable metallic stent placement for malignant colonic obstruction: A post‐hoc analysis of a multicenter study across Japan. Issue 1 (3rd September 2018) - Kuwai, Toshio; Yamaguchi, Toshiki; Imagawa, Hiroki; Yoshida, Shuntaro; Isayama, Hiroyuki; Matsuzawa, Takeaki; Yamada, Tomonori; Saito, Shuji; Shimada, Mamoru; Hirata, Nobuto; Sasaki, Takashi; Koizumi, Koichi; et al.
Abstract : Background and Aim: Colorectal cancer patients often present with large bowel obstruction. Elective placement of a self‐expandable metallic stent (SEMS) can relieve obstruction, but can be challenging. Previous studies have compared cases by outcomes only, but the present study investigated successful cases only to identify factors related to prolonged and difficult SEMS placement in patients with malignant colonic obstruction. Methods: A post‐hoc analysis of a multicenter clinical trial conducted between March 2012 and October 2013 at 46 facilities across Japan (UMIN000007953) was carried out; 511 patients who required SEMS placement for acute colorectal obstruction or symptomatic stricture secondary to malignant neoplasm were enrolled. Technical success rates and procedure times were recorded. Clinical and interventional parameters were investigated for their potential effect on procedure time by univariate and multivariate analyses. Results: Technical success rate of SEMS placement was 98%. Median procedure time was 30 (range, 4–170) min. In 27% of patients, procedure time exceeded 45 min, indicating technically difficult placement. Multivariate analyses showed significant associations between technically difficult placement and a ColoRectal Obstruction Scoring System (CROSS) score of 0 before SEMS placement (odds ratio [OR], 1.6; P < 0.05), tumor site in the right colon (OR, 2.5; P < 0.0001), stricture length ≥5 cm (OR, 2.2; P < 0.001), peritoneal carcinomatosis (OR, 1.7; P < 0.05), and multiple SEMS placement (OR, 8.0; P < 0.01). Conclusion: Clinicians must anticipate technical challenges in cases with peritoneal carcinomatosis, a CROSS score of 0, or expansive strictures; such cases require experienced clinicians to carry out SEMS placement.